Design Thinking FOREX in Islamic Law Perspective Inspiration of the Hadith of the Prophet SAW - Luthfi Adrian Maulana; Irwan Abdurrohman (Gunung Djati Conference Series, 2021)
This study aims to discuss the inspiration of the hadith about Forex Trading. This research method is qualitative through literature and field studies with the hadith design thinking approach. The results and discussion include Forex trading from an Islamic perspective, overcoming the economic crisis with the role of Forex trading during a pandemic, and the function and role of Forex trading in the economic field. This research concludes that the hadith has an inspirational message in innovative solutions in the field of Forex Trading to overcome the economic crisis during a pandemic.